Bridging Efficiency and Accuracy in Aviation Fuel Combustion Simulations with Reduced Kinetics - Passad, Martin (Department of Physics, Lund University, 2025)
Turning sustainable is one of the largest challenges facing the aviation sector. Switching to sustainable aviation fuel (SAF) instead of fossil fuels is a large piece of the sustainability puzzle, but there is no current SAF that is approved as a stand alone fuel. The road to a stand alone SAF is long and requires more diverse biofuels as well as more research on how biofuels combust. This thesis investigates how extinction phenomena of jet fuels are simulated in chemical kinetic combustion simulations, with a focus on extinction strain rate (ESR). ESR is a measure of how resistant a flame is to extinction. Surrogates are artificial mixtures made to emulate fuel characteristics. A surrogate formulation methodology was developed with an aim to be fast and simple, in order to efficiently simulate jet fuels. The surrogate was developed for use in a wide range of combustion simulations. The transport formulation in extinction simulations in the literature vary and an investigation into different transportation formulations concluded that mixture-average and multi-component formulations differ little in terms of ESR. Thermal diffusion on the other hand showed a large impact on both premixed and non-premixed ESR. Transport data of the fuel molecule was also shown to have a large impact on ESR, usually the ESR showed a larger sensitivity to diffusion parameters than kinetics. This is especially important for heavier hydrocarbons (HCs), such as those used in aviation fuels. There is less evaluations of heavy than for lighter HCs in the literature, which highlights the need for reliable methods of transport formulations of heavy and complex HCs such as those present in aviation fuels. The role of the transport data in extinction simulations are also not well understood. The effect of changing one parameter on the ESR does not always have a clear answer, as the problem is complex and multivariate.
Keywords: Combustion Kinetics; Sustainable Aviation Fuel; Extinction; n-Heptane; Diffusion